2015
DOI: 10.3390/genes6020417
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling during Appendage Development and Regeneration

Abstract: Regulatory networks that govern embryonic development have been well defined. While a common hypothesis supports the notion that the embryonic regulatory cascades are reexpressed following injury and tissue regeneration, the mechanistic regulatory pathways that mediate the regenerative response in higher organisms remain undefined. Relative to mammals, lower vertebrates, including zebrafish and newts, have a tremendous regenerative capacity to repair and regenerate a number of organs including: appendages, ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 97 publications
(252 reference statements)
0
30
0
Order By: Relevance
“…Therefore, our findings suggest that repression of these pathways in early stages of regeneration may be necessary and that precise timely release of inhibition ensures successful regeneration. It is interesting to note that the analysis did not reveal strong predictions for activation or repression of other pathways essential for limb regeneration, such as sonic hedgehog (shh) signaling (Singh et al, 2015). These other pathways may be downstream and act at later stages of regeneration (or are regulated post-transcriptionally).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings suggest that repression of these pathways in early stages of regeneration may be necessary and that precise timely release of inhibition ensures successful regeneration. It is interesting to note that the analysis did not reveal strong predictions for activation or repression of other pathways essential for limb regeneration, such as sonic hedgehog (shh) signaling (Singh et al, 2015). These other pathways may be downstream and act at later stages of regeneration (or are regulated post-transcriptionally).…”
Section: Discussionmentioning
confidence: 99%
“…In lower vertebrates, differentiated cells can revert to a fetal-like stage with high proliferative capacity to repair damaged tissue. Thereafter, redifferentiation into the adult cell types allows restoration of full tissue functionality ( Singh et al, 2015 ). Lineage-tracing approaches in the mouse have revealed that a similar process of de-differentiation can occur during epithelium repair in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that precocious progenitor differentiation, potentially as a result of abrogated Hh signaling, may be a significant mechanism underlying CHD. Hosoya et al, 2020;Ingham and Placzek, 2006;Ingham et al, 2011;Jiang and Hui, 2008;Lee et al, 2016;McMahon et al, 2003;Singh et al, 2015;Wallace, 2008). Global disruption of Hh signaling during embryogenesis causes pleiotropic developmental syndromes, including VACTERL syndrome, Gorlin Syndrome, holoprosencephaly and Greig cephalopolysyndactyly syndrome (Hui and Angers, 2011;McMahon et al, 2003;Ngan et al, 2012;Nieuwenhuis and Hui, 2005).…”
Section: Foxf1 Directly Represses a Cardiomyocyte Differentiation Promentioning
confidence: 99%